Durability of building materials and components - Delgado, J.M.P.Q; Freitas, Vasco Peixoto de (Building pathology and rehabilitation, 2013)
Durability of Building Materials and Components provides a collection of recent research works to contribute to the systematization and dissemination of knowledge related to the long-term performance and durability of construction and, simultaneously, to show the most recent advances in this domain. It includes a set of new developments in the field of durability, service life prediction methodologies, the durability approach for historical and old buildings, asset and maintenance management and on the durability of materials, systems and components. The book is divided in several chapters that intend to be a resume of the current state of knowledge for benefit of professional colleagues.